Detecting Well Casing Leaks in Bangladesh Using a Salt Spiking Method. Issue 1 (4th June 2014) - Stahl, M.O.; Ong, J.B.; Harvey, C.F.; Johnson, C.D.; Badruzzaman, A.B.M.; Tarek, M.H.; van Geen, A.; Anderson, J.A.; Lane, J.W.
Abstract We apply fluid‐replacement logging in arsenic‐contaminated regions of Bangladesh using a low‐cost, down‐well fluid conductivity logging tool to detect leaks in the cased section of wells. The fluid‐conductivity tool is designed for the developing world: it is lightweight and easily transportable, operable by one person, and can be built for minimal cost. The fluid‐replacement test identifies leaking casing by comparison of fluid conductivity logs collected before and after spiking the wellbore with a sodium chloride tracer. Here, we present results of fluid‐replacement logging tests from both leaking and non‐leaking casing from wells in Araihazar and Munshiganj, Bangladesh, and demonstrate that the low‐cost tool produces measurements comparable to those obtained with a standard geophysical logging tool. Finally, we suggest well testing procedures and approaches for preventing casing leaks in Bangladesh and other developing countries.